PEDAGOGICAL SKILLS IN THE PROCESS OF SPIRITUAL AND MORAL EDUCATION (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes the importance of pedagogical skills, its content and main components in the effective implementation of spiritual and moral education from a scientific point of view. The article explores the role of the teacher in the process of spiritual and moral education, his methodological and communicative skills, as well as the mechanisms of formation of moral values in students in the educational process. The results of the research show a strong relationship between pedagogical skills and the effectiveness of spiritual-moral education. At the same time, the article presents modern pedagogical approaches and practical recommendations that serve to strengthen moral education in the education system.